PENGARUH VARIASI PANJANG BENTANG BALOK PADA STRUKTUR RANGKA PEMIKUL MOMEN KHUSUS TERHADAP TINGKAT LAYAN/KINERJA STRUKTUR - Arie Wardhono (Universitas Negeri Yogyakarta, 2007)
AbstractBuilding structures have manystyles, forms andmodels that becomingseparatephenomenonfor civil engineer in analyzing its structure. One is structure configuration with length variationofbeam.The objection ofthis study is to know theperformance level ofstructure along with its elementto the variation ofbeam length to structure ductility, to know the global ductility that reached, andalso to get the comparison ofdesign target displacement to actual target displacement for everystructure model. Analysis will be conducted by comparing of 7 structures model in 2Dform withlength variation ofbeam on Special Moment Resisting Frame design. Seismic force analysis willbe done based on static equivalent analysis in seismic zone (WG) of6 as according to regulationofSNI 03-1726-2002 and ATC-40 and ofFEMA-356 as complement using SAP software 2000Nonlinear software: